2021
DOI: 10.1021/acsmacrolett.0c00808
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Suppression of a Droplet Impacting on a Supersolvophobic Surface by a Small Amount of Polymer Additives

Abstract: A small amount of polymer dissolved in a droplet suppresses droplet rebound when it impinges on a supersolvophobic surface. This work investigates impacting dynamics of a droplet of dilute polymer solution depending on the molecular weight and the concentration of the polymer by using multibody dissipative particle dynamics simulations. Either the long polymer or the high polymer concentration suppresses rebound of a droplet although its shear viscosity and the liquid–vapor surface tension are not different fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 23 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…Recently, we published the, to our best knowledge, first such simulation of an impacting droplet of a dilute polymer solution aided by multi-body dissipative particle dynamics (MDPD). 25 We confirmed the rebound suppression after the retraction stage, namely, at the hopping stage, with a certain choice of material (simulation parameters). The polymer adsorbed on the surface plays two roles in the rebound suppression.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…Recently, we published the, to our best knowledge, first such simulation of an impacting droplet of a dilute polymer solution aided by multi-body dissipative particle dynamics (MDPD). 25 We confirmed the rebound suppression after the retraction stage, namely, at the hopping stage, with a certain choice of material (simulation parameters). The polymer adsorbed on the surface plays two roles in the rebound suppression.…”
Section: Introductionsupporting
confidence: 65%
“…Several droplet impact experiments have been interpreted by the "slow-retraction" mechanism, in which the polymer deposited on the surface increases the friction between liquid and solid at phase 2, the retraction stage, i.e., polymer is suspected of slowing the horizontal motion of fluid, assuming that the surface is horizontally oriented. [14][15][16][17][18][19][20]33 On the other hand, our former study 25 and the experiment by Zang et al 21 found that the reduced rebound velocity can be explained by the resistance against the hopping motion. In this so-called "slow-hopping" mechanism, the polymer obstructs the vertical motion of the fluid.…”
Section: A Molecular Mechanisms Of Rebound Suppressionmentioning
confidence: 53%
See 3 more Smart Citations